SIGNIFICANCE OF ACHROMOBACTER XYLOSOXIDANS IN ACUTE INTESTINAL INFECTIONS - Nodira T. Yodgorova; Aminjon S. Ne’matov; Zukhra A. Nuruzova; Axmadjon O. Abdullayev (Central Asian Journal of Medicine, 2024)
In this article, we aim to provide information about a unique case that was first discovered in Uzbekistan from isolates of a patient with acute intestinal infection. A rarely identified microorganism, Achromobacter xylosoxydans, was detected using molecular genetic methods. Consequently, a literature review of this microorganism was conducted. It has been determined that Achromobacter xylosoxydans, as well as other Achromobacter species, can cause a wide range of infections in hosts with underlying diseases, as well as independent diseases of various organs and systems with severe complications. Their infrequent occurrence and continuously evolving taxonomy make it challenging to determine their clinical features, risk factors for infection, and adverse outcomes. Due to the antimicrobial resistance of Achromobacter species, they are difficult to treat.